Peranan Orang Tua dalam Meminimalisir Penggunaan Aplikasi Tiktok untuk Mengoptimalkan Perkembangan Belajar Siswa Sekolah Dasar - Kaila Sifana Kurniawati; Achmad Fathoni (Elementary Teacher Education Program, Majalengka University, 2024)
Tiktok is one of the social media that is well-known among the public and even children today. The Tiktok application is popular with children because by playing Tiktok children can find fun and don't get bored easily. So that many mothers now let their children play gadgets excessively so that children do not fuss without thinking about the negative impact. This study aims to describe the role of parents as educators, as motivators, as facilitators, as mentors in minimizing the negative impact of using the Tiktok application on grade IV elementary school students and to determine the role of parents in overcoming the addiction of grade IV elementary school students. The type of research used in this writing is descriptive qualitative. Data collection techniques carried out by in-depth interviews, observation, and documentation. This research tests the validity of the data using source triangulation and technique triangulation. In the results of this study, the role of parents in education as educators, motivators, facilitators, and mentors is very important. So it is necessary for the role of parents in minimizing the negative impact of using the Tiktok application on gadgets to optimize learning development. Ways for parents to assist children in using gadgets include 1) Limit Children's Time in Playing Tiktok. 2) Selection of safe content according to the age of the child. 3) Balance the Use of Gadgets with Home Activities. 4) Establish Rules for Using Gadgets for Children.